Periodic Fasting Treatment on Growth Performance and Feed Efficiency of Nile Tilapia (Oreochromis niloticus, GIFT) - Jacob Da Costa Pereira; Salustiano Zaret; Mateus Salvador; Kismiyati; Sapto Adriyono; Ahmad Shofy Mubarak; Mohammad Anam Al Arif (Journal of Basic Medical Veterinary, 2026)
Fasting is a feed management strategy that reduces feeding frequency without inhibiting fish growth. This strategy involves specific intervals of feed deprivation, allowing fish to exhibit increased appetite once feeding resumes. This study aimed to evaluate the effects of periodic fasting on the growth performance and feed efficiency of GIFT Nile tilapia, as well as to identify the most effective fasting pattern for optimal results. The research used a completely randomized design (CRD) with four treatments, each replicated three times: continuous feeding without fasting (K, control); two days of feeding followed by one day of fasting (2E1F); three days of feeding followed by one day of fasting (3E1F); and four days of feeding followed by one day of fasting (4E1F). The primary parameters observed were absolute weight gain (g), absolute length growth (cm), and feed efficiency. Data were analyzed using the Kruskal–Wallis test (p < 0.05), followed by post hoc comparisons using independent samples tests to determine significant differences among treatments. The results showed that periodic fasting had a significant effect (p < 0.05) on absolute weight gain, absolute length growth, and feed efficiency of GIFT Nile tilapia. The best performance was observed in treatment 4E1F (four days of feeding followed by one day of fasting), while the lowest performance occurred in treatment 2E1F (two days of feeding followed by one day of fasting).